Sociologies in Dialogue (Hanafi & Yi, editors. 2020): A Pursuit of Intellectual Equity in an Uneven World - Collares, Ana Cristina (2021)
HANAFI, Sari; YI, Chin-Chun. (Eds.). Sociologies in dialogue. Newcastle upon Tyne, UK: Sage, 2020